The Joint Research Centre’s Expertise in Nuclear Safeguards Sample Analysis - Hernández Ana María Sánchez; Buda Razvan; Casteleyn Karin; Commin Lorelei; D’Amati Francesco; Horta Joan; Le Terrier Arnaud; Mühleisen Artur; Stohr Sarah; Schorlé Hélène; Toma Magdalena; Zuñiga Martin Vargas; et al. (EPJ Web of Conferences)
The Joint Research Centre (JRC) in Karlsruhe, in partnership with the Directorate General for Energy (DG ENER), plays a critical role in ensuring the accurate analysis of nuclear materials, as mandated by the EURATOM Treaty. The Analytical Service at JRC Karlsruhe is dedicated to maintaining the highest standards of quality, accuracy, and traceability in its analytical measurements, with a focus on uranium and plutonium content and isotopic composition. Our laboratory is accredited according to ISO/IEC 17025 and has a proven track record of successful participation in numerous Inter-Laboratory Comparisons (ILCs), demonstrating our expertise and commitment to excellence in nuclear material analysis. We employ a range of analytical methods, including active and passive radiometric techniques and mass spectrometry, to ensure the lowest possible uncertainty in our results. Our laboratory has consistently achieved top performance in various ILCs, showcasing our ability to deliver high-quality results and our dedication to maintaining the highest standards of accuracy and reliability. This is a testament to our rigorous quality control processes and our commitment to staying at the forefront of nuclear material analysis. This paper provides insights into the factors that we believe have contributed to our top performance, including our rigorous quality control processes, our commitment to staff training and development, and our investment in state-of-the-art instrumentation. By sharing our experiences and best practices, we aim to contribute to the advancement of nuclear material accounting and control, safeguards verification, and non-proliferation efforts.